Increased White Matter Inflammation in Aging- and Alzheimer’s Disease Brain - Raj, Divya; Yin, Zhuoran; Breur, Marjolein; Doorduin, Janine; Holtman, Inge R.; Olah, Marta; Mantingh-Otter, Ietje J.; Van Dam, Debby; De Deyn, Peter P.; den Dunnen, Wilfred; Eggen, Bart J. L.; Amor, Sandra; et al. (Frontiers in Molecular Neuroscience, 2017)
Chronic neuroinflammation, which is primarily mediated by microglia, plays an essential role in aging and neurodegeneration. It is still unclear whether this microglia-induced neuroinflammation occurs globally or is confined to distinct brain regions. In this study, we investigated microglia activity in various brain regions upon healthy aging and Alzheimer’s disease (AD)-related pathology in both human and mouse samples. In purified microglia isolated from the aging mouse brain, we found a profound gene expression pattern related to pro-inflammatory processes, phagocytosis, and lipid homeostasis. Particularly in white matter microglia of 24-month-old mice, abundant expression of phagocytic markers including Mac-2, Axl, CD16/32, Dectin1, Cd11c, and Cd36 was detected. In white matter of human brain the first signs of inflammatory activity were already detected during middle age. Quantification of microglial proteins, such as CD68 (commonly associated with phagocytosis) and HLA-DR (associated with antigen presentation), in postmortem human white matter brain tissue showed an age-dependent increase in immunoreactivity already in middle-aged people (53.2 ± 2.0 yr), which was also detectable by non-invasive positron emission tomography (PET) imaging using [11C]-(R)-PK11195, a ligand that binds to activated microglia. Increased microglia activity was also prominently present in the white matter of human early-onset postmortem AD (EOAD) brains. Interestingly, microglia activity in the white matter of late-onset AD (LOAD) CNS was similar to that of the aged clinically-silent AD cases. These data indicate that microglia-induced neuroinflammation is predominant in the white matter of aging mice and humans as well as in EOAD brains. This white matter inflammation may contribute to the progression of neurodegeneration, and have prognostic value for detecting the onset and progression of aging and neurodegeneration.